Heterostyly in Mussaenda II. Pollen-stigma interaction in compatible and incompatible crosses - Siar, S. V.; Rosario, T. L.; Bajet, N.B.; Hernandez, J. E.; Villegas, V. N. (2001)
Heterostyly and its relation to incompatibility was investigated in Mussaenda cultivars of the pin morph type ('Doña Eva', 'Doña Esperanza', 'Queen Sirikit' and 'Lakambini') and the thrum morph type ('Mutya', 'Doña Luz', 'Baby Aurora' and 'Doña Trining'). A number of pollen grains adhered on the pin cultivars when these were used as female parents in hybridization and the pollen tubes penetrated the stigma down to the style. In contrast, when the thrum morphs were used as female parents, most pollen grains failed to germinate and were stuck on the stigmatic surface. In those that germinated, pollen growth was spindly and morphologically abnormal. In the stigmas from the thrum morphs, failure of the pollen grains to germinate freely was related to the short and collapsed stigmatic papillae and their inability to support and provide the necessary water and metabolites, specifically sucrose, to the metabolite-deficient trinucleate pollen grains.
Keywords: Mussaenda (plant); Plant morphology